Simplify -2(x - 5) + 4(9 + x).

1 answer

Starting with -2(x - 5):

Using the distributive property, we can multiply -2 by each term inside the parentheses:

-2(x) - (-2)(5)

This simplifies to:

-2x + 10

Now let's simplify 4(9 + x):

Again, we use the distributive property:

4(9) + 4(x)

This simplifies to:

36 + 4x

Now we can put these two parts together:

-2(x - 5) + 4(9 + x)

= (-2x + 10) + (36 + 4x)

= 2x + 46

So the simplified expression is 2x + 46.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions